German-Malaysian Insitute (GMI) / Hafizatul Huda Huzailing ... [et al.] - Hafizatul Huda, Huzailing; Norkhaleeda, Zulkipli; Muhammad Shahir Amani, Khalid; Muhammad Iqhmal Hakim, Norazmawi; Mohammad Aimullah, Zaini (2019)
German-Malaysian Institute is a private university college located at Jalan Ilmiah, Taman Universiti, 43000 Kajang, Selangor. The owner of this building is Majlis Amanah Rakyat (MARA). GMI was designated by Alizar Architect, with no special design concept that influenced the building. Most of GMI maintenance activities are done manually with no any special technologies features. GMI maintenance planning is done by doing routine, preventive and corrective maintenance and they are always ready to face any emergency breakdown that will occur. The Building Condition Assessment turn out rating is in fair condition and it is only use in the place that we can access, not to be judge from overall building space. Based on our findings, GMI successfully compliance with all requirements needed from Uniform Building by Law 1984 (UBBL 1984), Act 133 Street, Drainage & Building 1974, Occupational Safety & Health 1994 and Electricity Supply Act 1990 (ACT 447). Lastly, by through this case study we are able to coming out with cash flow and three years forecast of maintenance budget. Most of the income coming from MARA and Balanced Brought Forward (BBF) while most of the expenditure is spent to utilities bills and payment for outsource contractors. The building rating is fair, but the maintenance net profit is high. Therefore, the FMD team of GMI can use the money to repair and upgrade their building conditions for future result.